Addressing conflicts of interest regarding the vaccine in infectious disease outbreaks based on good governance for health approach: a policy brief - Nazanin Soleimani; Hamed Ghoshouni; Hakimeh Mostafavi; Mohammad Hossein Modiri; Mohammad Hasan Movahedian Attar; Seyed Masood Mousavi (BMC, 2023)
Abstract Background Infectious disease outbreaks pose a significant threat to public health, and achieving herd immunity highlights the importance of addressing conflicts of interest (COI) in vaccine development and policy-making. This policy brief aims to present policy options that address COI regarding vaccines in infectious disease outbreaks, based on good governance for health approach. Methods Our study used a scoping review methodology. We conducted a systematic search, which led to identifying 43 eligible articles. A qualitative approach (i.e., content analysis) was employed for data analysis, using "ATLAS.ti 9" software. The primary results underwent a process of cleaning, categorisation, and subsequent discussion in three sessions with the research team. Results Relationships between theindustry and "government/policymakers" as well as "academic institutions/researchers" are prominent origins of COI regarding the vaccine in infectious disease outbreaks. To address this issue, we present nine policy options that target both the root cause of the problem and the adoption of good governance for health approach. Conclusions The key principles of good governance for health, including, "Transparency", "The Rule of Law", "Effectiveness", "Efficiency", "Participation", "Consensus Orientation", "Equality", "Responsibility", "Responsiveness" and "Accountability" must be taken into account when formulating policy options to address COI regarding the vaccine in infectious disease outbreaks. The effectiveness of the policy options outlined in this policy brief should be assessed in practical contexts, as this evaluation may uncover the need for revisions.